Does Public Employment Affect Household Saving Rates? Evidence from Chinese Household Data - Can Xu; Andreas Steiner (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper investigates the impact of public employment on household saving rates in China using representative household-level data. After controlling for a series of variables such as income, risk attitude, financial literacy, and demographic factors, we show that households headed by public employees have higher saving rates than other households. This positive association holds after controlling for self-selection bias. Public employees are more likely to save for their children and they have a higher saving capacity than non-public employees due to better social security. Our results contribute to a better understanding of Chinese household saving rates, which is of great importance given their extremely high level in international comparison.
Keywords: D14; E24; H31; G51; 330; public employment; household saving rates; Chinese economy